Catalytic Treatment of Organic Solvent Vapor in a Baking Oven. Issue 1 (25th November 2021) - Inoue, Kenichiro
Abstract: A catalytic treatment for organic solvent vapor using the heat of a baking oven was investigated. A Pt/Al2 O3 catalyst showed high activity for toluene. A Co3 O4 ‐CeO2 catalyst preferentially oxidized ethyl acetate and butyl acetate, but by‐products were generated. These organic solvents produce high emissions from painting and printing ink in Japan. However, treating all three solvents simultaneously at low temperatures is difficult. In the present study, when a Pt/Co3 O4 ‐CeO2 catalyst was employed at oven temperatures of 230–250 °C, a gas containing toluene, ethyl acetate, and butyl acetate was able to be effectively treated with no carbon deposition. The application of the Pt/Co3 O4 ‐CeO2 catalyst enabled treatment in the oven using the oven's own heat. Abstract : A catalytic treatment method for organic solvent vapor exhausted from a baking oven used in painting and printing factories was investigated. A Pt/Al2 O3 catalyst showed high activity for toluene. A Co3 O4 ‐CeO2 catalyst preferentially oxidized ethyl acetate and butyl acetate. The combined Pt/Co3 O4 ‐CeO2 catalyst enabled treatment of the above solvents in a baking oven at 230–250 °C using its own heat.